ROLE OF DIMETHYL SULFATE ON BIOCHEMICAL CHARACTERISTICS OF Fragaria ananassa Duch UNDER SALINITY STRESS IN VITRO - S., Yasir S.; Hamad, R. M.; Neamah, S. I. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
The aims of this study were to evaluate the effect of four concentrations of Dimethylsulfate (DMS) 0%, 0.03%, 0.06% and 0.1% under four levels of salinity including 0, 30, 60 and 90 mmol NaCl L-1 on some biochemistry characters such as proline, hydrogen peroxide (H2O2), catalase (CAT), superoxide dismutase (SOD), chlorophyll a (Chl a), chlorophyll b (Chl b) and total chlorophyll. All treatments were distributed according to the factorial experiment using complete ro(CRD) with five replicates. Results revealed that 0.03% of DMS gave the highest proline of 2.08 mg g-1, H2O2 of 0.64 µM 100mg-1, catalase of 19.53 AU min-1g-1 and SOD of 116.8 IU 100mg-1. The control achieved the highest Chl a of35.75 mg g-1, Chl b of 23.38 mg g-1 and total chlorophyll of 79.00 mg g-1 . Furthermore, 30 mM NaCl L-1 possesses highest proline of 2.14 mg g-1, H2O2 of 0.62 µM 100mg-1, catalase of 19.38 AU min-1g-1 and SOD of 114.0IU 100mg-1. The non-saline plantlets (control) gave highest Chl.a of 33.00 mg g-1, Chl b 20.62 mg g-1. While 60 mmol NaCl L-1 gave biggest total chlorophyll of 74.75.